Method, component and application thereof for improving lubrication performance of tungsten carbide-based metal ceramic coating
By soaking the tungsten carbide-based cermet coating in the marine environment to form marine self-lubricating products, the problem of lack of lubrication function of the coating is solved, and the effect of significantly improving lubricating performance while maintaining high wear resistance is achieved.
Patent Information
- Application Number
- CN202411614205.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-13
AI Technical Summary
Tungsten carbide-based metal cermet coating lacks lubrication function in marine engineering equipment, resulting in severe wear of frictional materials, and the existing methods and processes may affect the mechanical properties of the coating.
The tungsten carbide-based cermet coating is placed in the marine environment for more than 1 month to form a dynamically evolved marine self-lubricating product, thereby improving the lubricating performance of the coating.
Through marine immersion treatment, the lubricating performance of the tungsten carbide-based metal cermet coating has been greatly improved, reducing the friction coefficient, forming a long-term and effective lubricating film, and having high wear resistance.
Smart Images

Figure CN119144955B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of surface modification, and in particular to a method for improving the lubrication performance of a tungsten carbide-based metal ceramic coating, a component and an application thereof. Background Art
[0002] The ocean area occupies the vast majority of the earth's surface area and contains rich resources to be mined. Typical marine engineering equipment, such as drilling platforms, oil and gas production equipment, and deep-sea mining systems, constitute the key infrastructure for the efficient development and large-scale utilization of marine resources. However, due to the complex and harsh marine environment, the components of the mechanical motion system of marine engineering equipment in service face serious friction and wear problems. According to statistics, about 60% of mechanical parts malfunction or fail due to wear caused by friction or poor lubrication. Good lubrication is one of the core technologies to extend the service life of moving parts and improve their operational reliability. At present, in engineering practice, motion mechanisms mostly use simple solid lubrication or grease lubrication. Solid lubricating materials have high friction noise and limited service life. Most liquid lubricants are insufficient in volatility, high temperature stability, mobility, and sealing requirements, and perform poorly in load-bearing capacity and stability.
[0003] In addition to adding lubricants, the selection and design of the coating material composition system is also an effective way to improve the tribological properties of materials. Among them, thermal sprayed tungsten carbide-based metal ceramic coatings represented by WC-Co, WC-Ni, and WC-Co-Cr are widely used in surface wear and corrosion protection of mechanical parts due to their high hardness, good toughness, and excellent wear and corrosion resistance. With the continuous improvement of coating performance requirements under various complex service conditions, especially in dealing with multiple harsh and complex service environments such as heavy loads and highly corrosive media, the development of cemented carbide coatings with stronger wear and corrosion resistance has become an urgent need to increase the service life of key components of marine engineering equipment.
[0004] However, although tungsten carbide-based metal ceramic coating has high wear resistance, it does not have lubrication function, so it causes great damage to the friction partner material. In order to reduce the wear of the partner material, in recent years, the introduction of solid lubricants into the spray powder to prepare a composite coating with lubrication properties has become a research hotspot. For example, Chinese patent publication CN111826568A discloses a method for improving the lubrication performance of WC-Co cemented carbide, which obtains WC-Co-graphite composite material by ball milling WC fine powder and high-purity Co powder and adding graphite powder. However, the preparation method has strict requirements on the content ratio of the powder, and the process flow is complicated. In addition, the addition of a lubricating phase during the spraying process will cause the mechanical properties of the coating, such as hardness and toughness, to decrease. Therefore, it is urgent to develop a simple, efficient and long-lasting method to improve the lubrication performance of tungsten carbide-based metal ceramic coating without affecting its own mechanical properties.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a method for improving the lubrication performance of tungsten carbide-based metal ceramic coatings, parts and components, and the application of the parts in wear-reducing and wear-resistant mechanical structures to improve the above-mentioned technical problems.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a method for improving the lubrication performance of a tungsten carbide-based metal ceramic coating, comprising: immersing the tungsten carbide-based metal ceramic coating in a marine environment for more than 1 month.
[0009] In an optional embodiment, the immersion is to completely immerse the tungsten carbide-based cermet coating in natural seawater.
[0010] In an alternative embodiment, the substrate for bonding with the tungsten carbide-based cermet coating is preferably a titanium alloy substrate.
[0011] In an optional embodiment, the tungsten carbide-based cermet coating is sprayed by a thermal spraying process.
[0012] In an optional embodiment, the thermal spraying process includes any one of low pressure plasma spraying, atmospheric plasma spraying, supersonic plasma spraying and supersonic flame spraying.
[0013] In an optional embodiment, the thermal spraying process is preferably supersonic flame spraying, and the spraying conditions include: oxygen flow rate of 800L / min~1000L / min, kerosene flow rate of 20L / min~40L / min, carrier gas flow rate of 4~12L / min, and powder feeding rate of 1.5~2r / min.
[0014] In an optional embodiment, after the tungsten carbide-based cermet coating is obtained by spraying through a thermal spraying process, the tungsten carbide-based cermet coating is polished and cleaned.
[0015] In an optional embodiment, the material of the tungsten carbide-based metal ceramic coating is selected from at least one of WC-Co, WC-CoCr, WC-Ni and WC-NiMoCrFeCo;
[0016] And / or, the thickness of the tungsten carbide-based metal ceramic coating is 100 μm to 300 μm.
[0017] In a second aspect, the present invention provides a component having a modified tungsten carbide-based metal ceramic coating, wherein the modified tungsten carbide-based metal ceramic coating is obtained by being treated by the method for improving the lubrication performance of the tungsten carbide-based metal ceramic coating according to the aforementioned embodiment.
[0018] In a third aspect, the present invention provides the use of the parts of the aforementioned embodiment in a wear-reducing and wear-resistant mechanical structure.
[0019] The present invention has the following beneficial effects:
[0020] (1) After soaking the tungsten carbide-based metal ceramic coating in a marine environment and taking out the coating sample, it was found that a marine self-lubricating product in a dynamic evolution appeared in the coating, which had a significant positive effect on the lubrication performance of the coating, and finally greatly improved the lubrication performance of the tungsten carbide-based metal ceramic coating. This method was discovered for the first time, and its true reliability was verified by experimental means. It achieved excellent adaptive lubrication ability without adding an additional lubricating phase, reduced the friction coefficient of the coating, and improved the lubrication performance, so that the thermal sprayed tungsten carbide-based metal ceramic coating can achieve high lubrication performance while having high wear resistance. In addition, the marine self-lubricating product produced in the tungsten carbide-based metal ceramic coating after being soaked in the ocean is in a dynamic evolution state of continuous outward seepage. During the friction process, it can continuously fill in the friction gap, continuously replenish the lubricant consumed by friction and wear, and ensure the long-term and effective lubrication performance of the coating.
[0021] (2) When the parts processed by this method are used in friction conditions, a friction film with low shear strength, high hardness, high elastic modulus and strong resistance to plastic deformation can be formed on the friction surface, thereby achieving the purpose of reducing the friction coefficient and reducing wear. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 The thermal spraying WC-NiMoCrFeCo powder components (inset) and coating preparation flow chart of Example 1 and Comparative Example 1 of the present invention;
[0024] Figure 2 This is a schematic diagram of the ocean immersion process of the WC-NiMoCrFeCo coating of Example 1 of the present invention;
[0025] Figure 3 This is a SEM microscopic morphology of the WC-NiMoCrFeCo coating of Comparative Example 1 of the present invention before being immersed in the ocean (a1 and a2 are the surfaces of Comparative Example 1, and b1 and b2 are the cross-sections of Comparative Example 1);
[0026] Figure 4 This is a SEM microscopic morphology of the WC-NiMoCrFeCo coating of Example 1 of the present invention after being immersed in the ocean (a1 and a2 are the surfaces of Example 1, and b1 and b2 are the cross-sections of Example 1);
[0027] Figure 5 EDS-mappings of the surface of the WC-NiMoCrFeCo coating of Comparative Example 1 of the present invention that has not been immersed in the ocean;
[0028] Figure 6 EDS-mappings of the cross section of the WC-NiMoCrFeCo coating of Comparative Example 1 of the present invention that has not been immersed in the ocean;
[0029] Figure 7 EDS-mappings of the surface of the WC-NiMoCrFeCo coating of Example 1 of the present invention after being immersed in the ocean;
[0030] Figure 8 EDS-mappings of the cross section of the WC-NiMoCrFeCo coating of Example 1 of the present invention after being immersed in the ocean;
[0031] Fig. 9 The dynamic evolution process of the self-lubricating product of the WC-NiMoCrFeCo coating of Example 1 of the present invention after being immersed in the ocean; (ac) initiation period; (df) growth period; (gi) rupture period;
[0032] Fig.10TEM image of the cross section of the WC-NiMoCrFeCo coating of Example 1 of the present invention after ocean immersion; (a) FIB preparation position of the test slice; (b) BF-TEM image of the slice; (c) BF-TEM image, elemental composition (At.%, inset) and EDS-mappings of the corresponding self-lubricating product film; (d) and (e) HR-TEM and FFT images of the selected area of the corresponding self-lubricating product film; (f) (Ⅰ-Ⅳ) corresponding 3D AOGF mapping;
[0033] Fig.11 This is a comparison chart of the friction coefficient of the WC-NiMoCrFeCo coatings of Examples 1-6 of the present invention and Comparative Examples 1-3;
[0034] Fig.12 The macroscopic morphology comparison diagram of Example 1 of the present invention and Comparative Example 1;
[0035] Fig.13 It is a comparison chart of the microhardness of the WC-NiMoCrFeCo coating of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0037] The following is a detailed description of a method, components and applications of the present invention for improving the lubrication performance of a tungsten carbide-based metal ceramic coating.
[0038] The inventor creatively discovered that by placing the tungsten carbide-based metal ceramic coating in a marine environment and immersing it for a period of time through the action of natural ocean currents, a dynamically evolving marine self-lubricating product can be formed in the coating, which has a significant positive effect on the lubrication performance of the coating, and ultimately greatly improves the lubrication performance of the tungsten carbide-based metal ceramic coating. At the same time, the marine self-lubricating product is in a dynamic evolution state of continuous outward seepage, and can continuously fill in the friction gap during the friction process, continuously replenishing the lubricant consumed by friction and wear, and ensuring the long-term and effective lubrication performance of the coating. More importantly, while improving the lubricity of the tungsten carbide-based metal ceramic coating, its own mechanical properties are not affected.
[0039] Some embodiments of the present invention also provide a method for improving the lubrication performance of a tungsten carbide-based cermet coating, comprising: placing the tungsten carbide-based cermet coating in a marine environment and immersing it for more than 1 month. It should be noted that sufficient marine immersion time is required to form sufficient marine self-lubricating products in the coating. The marine environment in the embodiments of the present invention refers to a natural marine environment, such as the East China Sea, the South China Sea, the Bohai Sea, and the Yellow Sea.
[0040] In order to make the parts have higher wear resistance and mechanical properties, and have better bonding with the tungsten carbide-based metal ceramic coating, in some embodiments, the substrate used for bonding with the tungsten carbide-based metal ceramic coating is preferably a titanium alloy substrate.
[0041] In some embodiments, the tungsten carbide-based cermet coating is sprayed by a thermal spraying process.
[0042] For reference, the thermal spraying process includes any one of low-pressure plasma spraying, atmospheric plasma spraying, supersonic plasma spraying, and supersonic flame spraying.
[0043] Further, in some embodiments, the thermal spraying process is preferably supersonic flame spraying, and the spraying conditions include: an oxygen flow rate of 800L / min~1000L / min, such as 800L / min, 850L / min, 900L / min, 950L / min or 1000L / min, etc., a kerosene flow rate of 20L / min~40L / min, such as 20L / min, 25L / min, 30L / min, 35L / min or 40L / min, etc., a carrier gas flow rate of 4~12L / min, such as 4L / min, 5L / min, 6L / min, 7L / min, 8L / min, 9L / min, 10L / min, 11L / min or 12L / min, and a powder feeding rate of 1.5~2r / min, such as 1.5r / min, 1.6r / min, 1.7r / min, 1.8r / min, 1.9r / min or 2.0r / min, etc.
[0044] Specifically, in some embodiments, after the tungsten carbide-based metal ceramic coating is obtained by thermal spraying, the tungsten carbide-based metal ceramic coating is polished and cleaned. Polishing can meet the roughness requirement of the ceramic coating, and cleaning can remove pollution and debris caused by the polishing process.
[0045] Exemplarily, the material of the tungsten carbide-based metal ceramic coating is selected from any one of WC-Co, WC-CoCr, WC-Ni and WC-NiMoCrFeCo.
[0046] In order to make the tungsten carbide-based metal ceramic coating have better effect and meet the requirements of modification treatment, in some embodiments, the thickness of the tungsten carbide-based metal ceramic coating is 100μm~300μm, for example, 100μm, 120μm, 150μm, 180μm, 200μm, 230μm, 250μm, 280μm or 300μm, etc.
[0047] Some embodiments of the present invention also provide a component having a modified tungsten carbide-based cermet coating, wherein the modified tungsten carbide-based cermet coating is obtained by being treated by the method for improving the lubrication performance of the tungsten carbide-based cermet coating of the aforementioned embodiment.
[0048] Some embodiments of the present invention also provide use of the parts of the aforementioned embodiments in a wear-reducing and wear-resistant mechanical structure.
[0049] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0050] Example 1
[0051] This embodiment provides a method for improving the lubrication performance of a tungsten carbide-based cermet coating, which specifically includes the following steps:
[0052] 1) A layer of WC-NiMoCrFeCo alloy coating was prepared on the surface of TC4 titanium alloy substrate by supersonic flame spraying process. The spraying raw material was commercial WC-NiMoCrFeCo powder (particle size of 21-54 μm), purchased from Höganäs Ltd, Sweden), and the coating thickness was 200 μm.
[0053] 2) The sprayed WC-NiMoCrFeCo coating was carefully polished to a roughness of 0.2 μm and ultrasonically cleaned to remove contamination and debris caused by the polishing process.
[0054] 3) The pretreated WC-NiMoCrFeCo coating was immersed in the marine environment of the South China Sea for 6 months.
[0055] The WC-NiMoCrFeCo powder components (inset) and the coating preparation process flow chart of Example 1 are shown in FIG. Figure 1 As shown, the corresponding WC-NiMoCrFeCo coating is immersed in the ocean process schematic diagram as shown Figure 2 shown.
[0056] Example 2
[0057] The only difference between this embodiment and embodiment 1 is that the WC-NiMoCrFeCo coating in step 3) is immersed in the marine environment of the South China Sea for less than 1 month.
[0058] Example 3
[0059] The only difference between this embodiment and embodiment 1 is that the WC-NiMoCrFeCo coating in step 3) is placed in the marine environment of the South China Sea and immersed for 12 months.
[0060] Example 4
[0061] The only difference between this embodiment and embodiment 1 is that the WC-NiMoCrFeCo coating in step 3) is placed in the marine environment of the Bohai Sea and immersed for 6 months.
[0062] Example 5
[0063] The only difference between this embodiment and embodiment 1 is that the WC-NiMoCrFeCo coating in step 3) is placed in the marine environment of the East China Sea and immersed for 6 months.
[0064] Example 6
[0065] The only difference between this embodiment and embodiment 1 is that the WC-NiMoCrFeCo coating in step 3) is placed in the marine environment of the Yellow Sea and immersed for 6 months.
[0066] Comparative Example 1
[0067] The difference between this comparative example and Example 1 is that only steps 1) and 2) are performed to obtain the WC-NiMoCrFeCo coating.
[0068] Comparative Example 2
[0069] This comparative example provides a method for improving the lubrication performance of a tungsten carbide-based cermet coating, which specifically comprises the following steps:
[0070] 1) A layer of WC-NiMoCrFeCo alloy coating with a thickness of 200 μm was prepared on the surface of TC4 titanium alloy substrate by supersonic flame spraying process.
[0071] 2) The sprayed WC-NiMoCrFeCo coating was carefully polished to a roughness of 0.2 μm and ultrasonically cleaned to remove contamination and debris caused by the polishing process.
[0072] 3) The pretreated WC-NiMoCrFeCo coating was placed in a neutral salt spray chamber for 6 months. According to the national standard (GBT10125 2021), the neutral salt spray test was carried out in an ATLAS-CCX cyclic salt spray corrosion tester. The mass fraction of the NaCl salt solution was 5%±1%, the spray stage temperature was (35±2) ℃, and the salt solution sedimentation rate was 1~3 mL / (80 cm 2h), place the sample on a V-shaped rack with the test surface at an angle of 20°±5° to the vertical direction, and spray alternately.
[0073] Comparative Example 3
[0074] This comparative example provides a method for improving the lubrication performance of a tungsten carbide-based cermet coating, which specifically comprises the following steps:
[0075] 1) A layer of WC-NiMoCrFeCo alloy coating was prepared on the surface of TC4 titanium alloy substrate by supersonic flame spraying process, and the coating thickness was 200 μm.
[0076] 2) The sprayed WC-NiMoCrFeCo coating was carefully polished to a roughness of 0.2 μm and ultrasonically cleaned to remove contamination and debris caused by the polishing process.
[0077] 3) The pretreated WC-NiMoCrFeCo coating was immersed in artificial seawater for 6 months. The composition of the artificial seawater solution is as follows: NaCl (24.531 g / L), MgCl2 (5.201 g / L), Na2SO4 (4.091 g / L), CaCl2 (1.161 g / L), KCl (0.695 g / L), NaHCO3 (0.201 g / L), KBr (0.101 g / L), H3BO3 (0.027 g / L), SrCl2·6H2O (0.025 g / L), and NaF (0.003 g / L).
[0078] Test example
[0079] The coatings of Comparative Example 1 and Example 1 were respectively subjected to microscopic inspection, and the SEM microscopic morphology comparison diagram (i.e., the comparison of the WC-NiMoCrFeCo coating before and after being immersed in the ocean) is shown as follows: Figure 3 and Figure 4 shown. Figure 3 In the figure, a1 and a2 are surfaces of Comparative Example 1, and b1 and b2 are cross sections of Comparative Example 1. Figure 4 In the figure, a1 and a2 are surfaces of Example 1, and b1 and b2 are cross sections of Example 1.
[0080] The coatings of Comparative Example 1 and Example 1 were further analyzed by X-ray energy spectrum elemental imaging analysis technology. The EDS-mappings of the surface and cross-section of the coating of Comparative Example 1 are as follows: Figure 5 and Figure 6 As shown, the EDS-mappings of the surface and cross section of the coating of Example 1 are as follows Figure 7 and Figure 8 shown.
[0081] By comparing the microscopic morphology and element distribution of the embodiment and comparative example 1, it can be observed that the coating after immersion in seawater has obvious enrichment of self-lubricating products, which are evenly distributed in the coating, and the products are mainly composed of Ni, Cl and O elements.
[0082] The dynamic evolution of the self-lubricating product of the WC-NiMoCrFeCo coating of Example 1 after being immersed in the ocean is shown in FIG. Fig. 9 As shown in the figure, it can be seen that the self-lubricating product is in a constantly changing dynamic evolution state. The cross section of the coating after immersion was observed by in-situ SEM for 30 days (720h), and the observation position was selected near the larger holes in the coating. The figure shows the full cycle state of the corrosion product from the initial initiation and seepage to the final growth and rupture. The entire dynamic evolution cycle of the reaction product is divided into three stages, the first is the initiation stage, the second is the growth stage, and the third is the expansion and rupture stage.
[0083] In order to further characterize the reaction products at the microscopic scale, TEM tests and analysis were performed on the coatings after ocean immersion. The FIB preparation position of the slices selected for TEM testing was at the interface between the reaction products, the coating and the substrate. Fig.10 (a) is to observe the structural composition of marine self-lubricating products and whether there is any enrichment of special elements or substances at the interface. Fig.10 TEM image of the cross section of the WC-NiMoCrFeCo coating of Example 1 after being immersed in the ocean; Fig.10 In the figure, (a) is the FIB preparation position of the test slice; (b) is the BF-TEM image of the slice; (c) is the corresponding BF-TEM image, elemental composition (At.%, inset) and EDS-mappings of the self-lubricating product film; (d) and (e) are the corresponding HR-TEM and FFT images of the selected area of the self-lubricating product film; (f) (Ⅰ-Ⅳ) corresponds to the 3D AOGF mapping. Fig.10 It can be seen that the self-lubricating product film is a structure in which nano-scale crystal particles are wrapped by amorphous phase materials, and the crystal particles are mainly composed of NiCl2, NiO and Ni(OH)2. Its unique layered structure can provide effective lubrication for the coating.
[0084] The friction coefficient of the WC-NiMoCrFeCo coatings obtained in Examples 1-6 and Comparative Examples 1-3 was tested (tested according to ASTM G133-22 standard, with a sliding speed of 9 cm / s and a load of 9 N). The results are as follows: Fig.11As shown. It can be seen from the figure that the WC-NiMoCrFeCo coating of comparative example 1 is the coating before being immersed in the ocean, and its friction coefficient is about 0.35. The WC-NiMoCrFeCo coatings of Examples 1, 3-6 are coatings after being immersed in different ocean areas for more than 1 month, and their friction coefficients are reduced by 70% compared with before immersion, reduced to about 0.1. The WC-NiMoCrFeCo coating of Example 2 is a coating after being immersed in different ocean areas for less than 1 month, and its friction coefficient is reduced compared with before immersion, but the friction curve is very unstable. The friction coefficient of the coating of comparative example 2 after salt spray treatment is about 0.3, and the friction coefficient is only reduced by about 14%. The friction coefficient of the coating of comparative example 3 after being immersed in an artificial seawater environment is about 0.28, and the friction coefficient is only reduced by about 20%. Among them, the macroscopic morphology comparison diagram of the coating of comparative example 1 and the coating of Example 1 is as follows: Fig.12 As shown, from Fig.12 It can be seen that the coating of Example 1 can be clearly seen to have self-lubricating properties, and when the same force is applied to the surface, the wear marks of the coating of Example 1 are shallower.
[0085] The microhardness test of the WC-NiMoCrFeCo coatings of Comparative Example 1 and Example 1, i.e., the coatings before and after ocean immersion, is performed, and the results are as follows: Fig.13 As shown, from Fig.13 It can be seen that compared with the coating of comparative example 1 before ocean immersion, the decrease in microhardness of the coating of example 1 is not obvious.
[0086] In summary, the embodiments of the present invention have the following advantages:
[0087] (1) The thermal sprayed tungsten carbide-based metal ceramic coating was used as a template and immersed in a marine environment. After the coating sample was taken out, it was found that a dynamically evolving marine self-lubricating product appeared in the coating, which had a significant positive effect on the lubrication performance of the coating, and ultimately greatly improved the lubrication performance of the tungsten carbide-based metal ceramic coating. This method was discovered for the first time, and its true reliability was verified by experimental means. It achieved excellent adaptive lubrication ability without adding an additional lubricating phase, reduced the friction coefficient of the coating, and improved the lubrication performance, thereby achieving high wear resistance and high lubrication performance for the thermal sprayed tungsten carbide-based metal ceramic coating.
[0088] (2) When the method of improving the lubrication performance of tungsten carbide-based metal ceramic coating is applied to friction conditions, a friction film with low shear strength, high hardness, high elastic modulus and strong resistance to plastic deformation can be formed on the friction surface, thereby achieving the purpose of reducing the friction coefficient and reducing wear.
[0089] (3) The marine self-lubricating products produced in the tungsten carbide-based metal ceramic coating after immersion in the ocean are in a dynamic evolution state of continuous outward seepage. During the friction process, they can continuously fill in the friction gaps and continuously replenish the lubricants consumed by friction and wear, thus ensuring the long-term and effective lubrication performance of the coating.
[0090] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for improving the lubrication performance of a tungsten carbide-based cermet coating, characterized in that: It includes: The tungsten carbide-based metal ceramic coating is placed in a marine environment and immersed for more than 1 month, and the tungsten carbide-based metal ceramic coating after immersion contains a marine self-lubricating product mainly composed of Ni, Cl and O elements; The immersion is to completely immerse the tungsten carbide-based metal ceramic coating in natural seawater; The material of the tungsten carbide-based metal ceramic coating is selected from at least one of WC-Ni or WC-NiMoCrFeCo; The tungsten carbide-based metal ceramic coating is obtained by thermal spraying; After the tungsten carbide-based metal ceramic coating is sprayed by the thermal spraying process, the tungsten carbide-based metal ceramic coating is polished and cleaned.
2. The method for improving the lubrication performance of tungsten carbide-based cermet coating according to claim 1, characterized in that: The thermal spraying process includes any one of low pressure plasma spraying, atmospheric plasma spraying, supersonic plasma spraying and supersonic flame spraying.
3. The method for improving the lubrication performance of tungsten carbide-based cermet coating according to claim 2, characterized in that: The thermal spraying process is supersonic flame spraying, and the spraying conditions include: oxygen flow rate is 800L / min~1000L / min, kerosene flow rate is 20L / min~40L / min, carrier gas flow rate is 4~12L / min, and powder feeding rate is 1.5~2r / min.
4. The method for improving the lubrication performance of tungsten carbide-based cermet coating according to any one of claims 1 to 3, characterized in that: The thickness of the tungsten carbide-based metal ceramic coating is 100 μm to 300 μm.
5. A component, characterized in that: The invention has a modified tungsten carbide-based metal ceramic coating, wherein the modified tungsten carbide-based metal ceramic coating is obtained by being treated by the method for improving the lubrication performance of the tungsten carbide-based metal ceramic coating according to any one of claims 1 to 4.
6. Use of the component as claimed in claim 5 in a wear-reducing and wear-resistant mechanical structure.
Citation Information
Patent Citations
WC-6Co-graphite self-lubricating hard alloy preparation method
CN111826568A